2021
DOI: 10.3389/fnhum.2021.739333
|View full text |Cite
|
Sign up to set email alerts
|

40-Hz Blue Light Changes Hippocampal Activation and Functional Connectivity Underlying Recognition Memory

Abstract: Research on light modulation has typically examined the wavelength, intensity, and exposure time of light, and measured rhythm, sleep, and cognitive ability to evaluate the regulatory effects of light variables on physiological and cognitive functions. Although the frequency of light is one of the main dimensions of light, few studies have attempted to manipulate it to test the effect on brain activation and performance. Recently, 40-Hz light stimulation has been proven to significantly alleviate deficits in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 74 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…Different light wavelengths (i.e., colors) were tested, with some groups reporting enhanced gamma brain activity with red light [18], or enhanced connectivity with violet light as compared to white light [20]. Blue light was also used to induce 40 Hz brain activity and was shown to increase hippocampal and visual cortex activation using functional magnetic resonance imaging (fMRI) measures, though this study did not have a white light stimulation arm [21]. Of interest, invisible spectral flicker at 40 Hz was also shown to induce 40 Hz brain activity and was comparable in engaging cortical brain activation to flickering white light at the same frequency [22].…”
Section: The Effects Of Gamma Sensory Stimulation In Patients With Al...mentioning
confidence: 99%
See 1 more Smart Citation
“…Different light wavelengths (i.e., colors) were tested, with some groups reporting enhanced gamma brain activity with red light [18], or enhanced connectivity with violet light as compared to white light [20]. Blue light was also used to induce 40 Hz brain activity and was shown to increase hippocampal and visual cortex activation using functional magnetic resonance imaging (fMRI) measures, though this study did not have a white light stimulation arm [21]. Of interest, invisible spectral flicker at 40 Hz was also shown to induce 40 Hz brain activity and was comparable in engaging cortical brain activation to flickering white light at the same frequency [22].…”
Section: The Effects Of Gamma Sensory Stimulation In Patients With Al...mentioning
confidence: 99%
“…Multiple studies have shown that gamma sensory stimulation can increase cerebral cortical activity in different brain areas as measured by fMRI, positron emission tomography (PET), and EEG recordings. In a study of 42 cognitively normal adults, a single session of 40 Hz blue light increased hippocampal and visual cortex activation as measured by task‐based fMRI [21]. However, after this single stimulation, there were no changes in response accuracy or response time despite increased brain activation.…”
Section: The Effects Of Gamma Sensory Stimulation In Patients With Al...mentioning
confidence: 99%
“…Additionally, an EEG study showed that an increase was found in the connectivity between dorsolateral prefrontal and visual cortices under rhythmic visual stimulation (6‐, 10‐, 15‐, and 40‐Hz) compared with no increase could be found in no flicker condition (You et al, 2020 ). Forty‐hertz blue light stimulation has been shown to activate the visual cortex and hippocampus, improving the functional connectivity between the hippocampus and superior parietal lobe while decreasing the functional connectivity between the hippocampus and the default mode network (DMN), according to a functional magnetic resonance imaging (fMRI) study (Lin et al, 2021 ). Meanwhile, 40‐Hz light flicker could alter microstate metrics representing activation or deactivation states of brain networks with different functions and adjust functional state of brain networks to make them work (Zhang et al, 2021 ).…”
Section: Basic Principles and Mechanisms Of Audiovisual Stimulationmentioning
confidence: 99%
“…Herrmann ( 2001 ) observed that when flicker light stimulation frequency was set from 1 to 100 Hz in 1‐Hz steps, event‐related potentials presented steady‐state potentials with significant resonance phenomena around 10, 20, 40, and 80 Hz in 10 healthy volunteers. In the current state of clinical practice, studies have been mostly conducted with 40‐Hz light stimulation on cognitive function (Lin et al, 2021 ; You et al, 2020 ; Zhang et al, 2021 ). Specifically, light flickering at 34–38 Hz with high‐intensity red or white light has been shown to entrain stronger and wider gamma oscillations than lower intensity light stimulation (Jones et al, 2019 ; Lee et al, 2021 ; Noda et al, 2021 ).…”
Section: Basic Principles and Mechanisms Of Audiovisual Stimulationmentioning
confidence: 99%
“…It was found that tACS at specific frequencies may lead to entrainment concussion at the target stimulation frequency ( Kasten and Herrmann, 2017 ). Enhancing brain gamma-band wave activity can more directly enhance cognitive function or modulate the neuropathology of cognitive dysfunction ( Kim et al, 2021 ; Lin et al, 2021 ; Yu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%